2022
DOI: 10.24034/j25485024.y2022.v6.i4.4602
|View full text |Cite
|
Sign up to set email alerts
|

Hexa Helix: Kolaborasi Quadruple Helix Dan Quintuple Helix Innovation Sebagai Solusi Untuk Pemulihan Ekonomi Pasca Covid-19

Abstract: Pandemi COVID-19 telah membawa dampak serius terhadap krisis kesehatan, ekonomi, transportasi dan industri lainnya. Diberlakukannya lockdown atau PSBB jelas berdampak terganggunya operasional berbagai sektor ekonomi. Tujuan dilakukannya penelitian ini untuk mendeskripsikan konsep kolaborasi Quadruple Helix dan model Quintuple Helix Innovation bagian dari inisiatif kolaborasi, inovasi dan sinergi antar multi aktor untuk membantu menemukan solusi sebagai upaya pemulihan ekonomi nasional pasca COVID-19 dalam meng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…Muhyi et al [21] examined the penta helix collaboration model in developing leading industrial centers in the city of Bandung Budhi, [22], researching the tourism industry in the Province of Bali. Meanwhile, by Wahdiniwaty et al, [23] and Firmansyah et al, [24] The results of other studies found that there were other factors causing the failure of poverty alleviation that were not included in planning a deep poverty prevention program, so that awareness of participating in poverty reduction or making efforts to leave the poverty zone was low. Feeling poor or on the poverty line does not affect their lifestyle, in a new methodology for multidimensional poverty measurement based on the capability approach, showed that the government only focused on manufacturing policies without considering the conditions of the poor.…”
Section: Resultsmentioning
confidence: 99%
“…Muhyi et al [21] examined the penta helix collaboration model in developing leading industrial centers in the city of Bandung Budhi, [22], researching the tourism industry in the Province of Bali. Meanwhile, by Wahdiniwaty et al, [23] and Firmansyah et al, [24] The results of other studies found that there were other factors causing the failure of poverty alleviation that were not included in planning a deep poverty prevention program, so that awareness of participating in poverty reduction or making efforts to leave the poverty zone was low. Feeling poor or on the poverty line does not affect their lifestyle, in a new methodology for multidimensional poverty measurement based on the capability approach, showed that the government only focused on manufacturing policies without considering the conditions of the poor.…”
Section: Resultsmentioning
confidence: 99%
“…To be able to comprehensively improve business performance in the era of the digital economy, even from time to time it is necessary to have continuous innovative cooperation among interested actors in order to improve digital readiness and the success of business digital transformation (go digial) in realizing the fulfillment of customer needs and satisfaction as the main market orientation, where the environment and information on competitors' behavior also need to get attention and become one of the considerations important in every decision making regarding the plan and strategy to be carried out. The existence of adaptive cooperation with interested actors through the circulation of innovative collaborations well established in healthy sustainable business practices can create resilience, development and increase business competitiveness with better economic performance (Firmansyah, Suherman, et al, 2022;.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, at that time, Indonesia's payment system was still dominated by cash. According to Firmansyah, around 90% of payments were made in cash in 2019 [26]. Meanwhile, digital payments have increased the average transaction value per user.…”
Section: Introductionmentioning
confidence: 99%